2018
DOI: 10.1021/acs.molpharmaceut.7b00891
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Barriers for Nicotine and Mannitol in Porcine Buccal Mucosa Studied by High-Resolution MALDI Mass Spectrometry Imaging

Abstract: Improved nicotine permeability across buccal mucosa may enable more effective oromucosal nicotine replacement therapy products. It is essential to know the location and composition of the main barrier for drug diffusion to enhance the drug permeability. Matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a rapidly evolving technique that can be used to image the spatial distribution of drugs and drug metabolites in tissue cryo-sections, without prior labeling of the drug. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…MALDI-MSI has been demonstrated to provide enough spatial resolution to be useful in providing qualitative drug distribution and penetration information on different types of tissues, 4,5,29,30 but it is not the ideal technique for quantification. From the present results, it thus cannot be inferred which of the three active drug substances is actually present at the highest concentration in the deeper layers.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-MSI has been demonstrated to provide enough spatial resolution to be useful in providing qualitative drug distribution and penetration information on different types of tissues, 4,5,29,30 but it is not the ideal technique for quantification. From the present results, it thus cannot be inferred which of the three active drug substances is actually present at the highest concentration in the deeper layers.…”
Section: Discussionmentioning
confidence: 99%
“…The intercellular lipid content is migrated to the apical cell surface to fuse with cell membrane and the lipid content is discharged into intercellular space to form a barrier of 200 µm superficial layer [11]. Marxen et al [16] reported that epithelium acts as a strong barrier for the permeation of nicotine and mannitol across the porcine buccal epithelium and buccal submucosa. Nicotine permeability at submucosa (P app,submucosa = 2.41 × 10 -5 ± 0.17 × 10 -5 cm/s; thickness = 635 ± 55 µm) was significantly higher than the epithelium (P app,epithelium = 1.20 × 10 -5 ± 0.24 × 10 -5 cm/s; thickness = 423 ± 46 µm), irrespective of the thickness.…”
Section: Oral Mucosamentioning
confidence: 99%
“…For these methods, the solution is removed from the receptor chamber at pre-determined time points to measure the drug permeation over time using a UV spectrophotometer or HPLC. More recently, the localisation of permeants within the oral mucosa itself has been visualised down to a micrometre scale resolution using matrix-assisted laser desorption ionisation-mass spectrometry imaging (MALDI-MSI) on sectioned tissue [ 84 ].…”
Section: Electrospun Mucoadhesive Materialsmentioning
confidence: 99%